PENGARUH POFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Tia Fatmawati, 13.05.52.0082; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2018)
Globalization encourages the development of increasingly fierce business competition, with the full number of emerging new companies emerging. An important goal of establishing a company is to increase the value of the company. The value of the company can be seen from the companys annual financial statements, by utilizing the financial statement information is expected investors can predict the performance and value of the company. This research is to know the influence of ROA to company with CSR and GCG as moderation variable. The sample of the research is 50 companies that are doing CGPI survey which listed in BEI period 2013-2016 by using purposive sampling. The method of analysis used in this study is multiple regression with moderate regression analysis model with the base of absolute difference. This research is conducted at Indonesia Stock Exchange and access annual report at www.idx.co.id. The results of this study showed ROA has a positive effect on the company. CSR disclosure is significant to the company. GCG does not affect the company. CSR does not moderate the effect of ROA on corporate value with. GCG moderates the effect of ROA on companies with significant negative results.Keyword : ROA, CSR, GCG, Nilai Perusahaan.